Evidence of negative energy balance using doubly labelled water in elite Kenyan endurance runners prior to competition - Fudge, B. W.; Westerterp, K. R.; Kiplamai, F. K.; Onywera, V. O.; Boit, M. K.; Kayser, B.; Pitsiladis, Y. P. (British Journal of Nutrition, 2006)
Previous studies have found Kenyan endurance runners to be in negative energy balance during training and prior to competition. The aim of the present study was to assess energy balance in nine elite Kenyan endurance runners during heavy training. Energy intake and expenditure were determined over 7 d using weighed dietary intake and doubly labelled water, respectively. Athletes were on average in negative energy balance (mean energy intake 13 241 (SD 1330) kJ/d v. mean energy expenditure 14 611 (SD 1043) kJ/d; P=0·046), although there was no loss in body mass (mean 56·0 (SD 3·4) kg v. 55·7 (SD 3·6) kg; P=0·285). The calculation of underreporting was 13% (range -24 to +9%) and almost entirely accounted for by undereating (9% (range -55 to +39 %)) as opposed to a lack of significant underrecording (i.e. total water intake was no different from water loss (mean 4·2 (SD 0·6) l/d v. 4·5 (SD 0·8) l/d; P=0·496)). Fluid intake was modest and consisted mainly of water (0·9 (SD 0·5) l/d) and milky tea (0·9 (SD 0·3) l/d). The diet was high in carbohydrate (67·3 (SD 7·8) %) and sufficient in protein (15·3 (SD 4·0) %) and fat (17·4 (SD 3·9) %). These results confirm previous observations that Kenyan runners are in negative energy balance during periods of intense training. A negative energy balance would result in a reduction in body mass, which, when combined with a high carbohydrate diet, would have the potential in the short term to enhance endurance running performance by reducing the energy cost of running.